Immunosenescence and ACE2 protein expression: Association with SARS-CoV-2 in older adults - Gustavo Acosta Altamirano; Carlos E Miguel Rodríguez; María del Rocío Reyes-Montes; Esperanza Duarte-Escalante; Rocío Acosta-Reyes; Carlos U Torres-Estrella; Omar E Valencia-Ledezma (Open Journal of Asthma - Peertechz Publications, 2022)
At the end of 2019, in Wuhan, China, an outbreak of cases of respiratory tract infection emerged and its progressive infection mainly affects adults, generating many cases of pneumonia. A type of coronavirus named SARS-CoV-2, with genomic similarity to SARS-CoV and MERS-CoV, was identified as the etiological agent. The evolution of this pandemic has made it possible to verify the similarity in the pathophysiological mechanisms between these three viruses, identifying the Angiotensin-Converting protein-Enzyme 2 (ACE2) as the primary receptor for SARS-CoV-2. This age group is more prone to developing extrapulmonary complications from SARS-CoV-2 since the clinical and pathological findings suggest a particular relationship between greater expression of ACE2 and the comorbidities of chronic degenerative diseases and the greater expression of ACE2 at the level of the respiratory tract. It has also revealed the mechanisms by which the virus evades the innate immune response and the Th1-type adaptive response. The objective of this work was to analyze immunosenescence and its relationship with SARS-CoV-2 infection, through the review of the most recent articles (2021-2022), which describes the senescent state of the elderly. In addition, it intends to highlight the probable causes for which the most vulnerable population group (adults over 60 years of age) is more prone to presenting complications during the infection.